Method construction of reinforcement concrete pile / Muhammad Faiz Yaacob - Yaacob, Muhammad Faiz (Universiti Teknologi MARA, Perak, 2013)
A building is generally composed of a superstructure above the ground and a substructure which forms the foundation below ground level. The foundations transfer and spread the loads from a structure's columns and walls in to the ground. This report briefly describes about all the process and method involved in reinforced concrete (RC) pile work that carried on at residential area based on interview, observation, searching internet and reading book. This report prepared based on the five months working experience at the construction site. Two proposed objective been highlight is to understand the installation procedure, process, and to identify material, plant and machineries used for RC pile. This report divided by several parts which started with the company background and construction project background. Based on the experience, RC pile work is not easy as it looks in terms of its construction process. However, it is more economical and faster to construct compared to other types of pile foundation. The method of embedded RC piles is using a hydraulic piling machine. Furthermore, all the machineries, plants and equipment's that involved in RC pile construction also are study. During the RC pile work, has a small number of problem and a few suggestion that believe can overcome the problem occur stated herein. As a conclusion, this report should expose to readers in details about the process and method involved in RC pile work.